Endometrial CXCL13 Expression Is Cycle Regulated in Humans and Aberrantly Expressed in Humans and Rhesus Macaques With Endometriosis. (April 2015) - Franasiak, Jason M.; Burns, Katherine A.; Slayden, Ov; Yuan, Lingwen; Fritz, Marc A.; Korach, Kenneth S.; Lessey, Bruce A.; Young, Steven L.
C-X-C ligand 13 (CXCL13), a regulator of mucosal immunity, is secreted by human endometrial epithelium and may be involved in embryo implantation. However, cyclic expression of human endometrial CXCL13 in health and disease is not well studied. This study examines cycle stage-specific endometrial CXCL13 expression in normal humans when compared to those with biopsy-confirmed, stage 1 to 4 endometriosis using real-time reverse transcriptase, real-time polymerase chain reaction and immunohistochemistry. Eutopic endometrial CXCL13 expression was also compared between normal, control Rhesus macaques, and macaques with advanced endometriosis. In healthy women, CXLC13 messenger RNA expression was minimal in the proliferative phase and maximal in the secretory phase. However, in the presence of endometriosis, proliferative-phase endometrial expression markedly increased in both humans and rhesus subjects ( P < .05). The cross-species and cross-stage concordance suggests a pathophysiologic role for CXCL13 in endometriosis and its use as a biomarker for disease.